2022
DOI: 10.1111/pedi.13448
|View full text |Cite
|
Sign up to set email alerts
|

The emotional well‐being of parents with children at genetic risk for type 1 diabetes before and during participation in the POInT ‐study

Abstract: Introduction: This study examined the emotional impact that parents experience when confronted with an increased genetic risk of type 1 diabetes (T1D) in their child. Population-based screening of neonates for genetic risk of chronic disease carries the risk of increased emotional burden for parents.Methods: Information was collected using a well-being questionnaire for parents of infants identified as having an increased risk for T1D in a multinational research study. Parents were asked to complete this quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(88 reference statements)
1
0
0
Order By: Relevance
“…Overall, the clinical presentation of children participating in the population-based Fr1da screening was comparable to that of children diagnosed with presymptomatic type 1 diabetes by islet autoantibody screening in natural history studies [7,11], or clinical trials [38], and similarly with respect to stress and anxiety levels in parents in response to screening. Previous findings from the Fr1da study indicated that psychological stress scores were transiently elevated in mothers of children diagnosed with presymptomatic type 1 diabetes in the Fr1da screening and that the distress reported by the families was low or moderate in the majority of families [18], consistent with findings in children diagnosed with islet autoantibodies in natural history studies [39,40] and in parents of children identified with an increased genetic risk for type 1 diabetes [41,42]. With an appropriate education and care programme, islet autoantibody screening and a diagnosis of presymptomatic type 1 diabetes appear unlikely to lead to the level of parental stress observed in families of children diagnosed with stage 3 type 1 diabetes without prior screening [18].…”
Section: Discussionsupporting
confidence: 75%
“…Overall, the clinical presentation of children participating in the population-based Fr1da screening was comparable to that of children diagnosed with presymptomatic type 1 diabetes by islet autoantibody screening in natural history studies [7,11], or clinical trials [38], and similarly with respect to stress and anxiety levels in parents in response to screening. Previous findings from the Fr1da study indicated that psychological stress scores were transiently elevated in mothers of children diagnosed with presymptomatic type 1 diabetes in the Fr1da screening and that the distress reported by the families was low or moderate in the majority of families [18], consistent with findings in children diagnosed with islet autoantibodies in natural history studies [39,40] and in parents of children identified with an increased genetic risk for type 1 diabetes [41,42]. With an appropriate education and care programme, islet autoantibody screening and a diagnosis of presymptomatic type 1 diabetes appear unlikely to lead to the level of parental stress observed in families of children diagnosed with stage 3 type 1 diabetes without prior screening [18].…”
Section: Discussionsupporting
confidence: 75%
“…The psychological difficulties and burdens faced by parents can influence their children's emotions and disease management, which in turn can impact adherence to treatment [20,25]. Therefore, it is crucial to alleviate the burdens of parents caring for very young children with diabetes, as their well-being is intrinsically linked to their children's psychological, physical, and social development [26].…”
mentioning
confidence: 99%